Psychosocial functioning in children with neurodevelopmental disorders and externalizing behavior problems. (February 2015) - Arim, Rubab G.; Kohen, Dafna E.; Garner, Rochelle E.; Lach, Lucyna M.; Brehaut, Jamie C.; MacKenzie, Michael J.; Rosenbaum, Peter L.
Abstract Purpose: This study examines psychosocial functioning in children with neurodevelopmental disorders (NDDs) and/or externalizing behavior problems (EBPs) as compared to children with neither condition. Methods: The longitudinal sample, drawn from the Canadian National Longitudinal Survey of Children and Youth, included children who were 6 to 9 years old in Cycle 1 who were followed-up biennially in Cycles 2 and 3 (N = 3476). The associations between NDDs and/or EBPs, child and family socio-demographic characteristics and parenting behaviors (consistency and ineffective parenting), were examined across several measures of child psychosocial functioning: peer relationships, general self-esteem, prosocial behavior and anxiety-emotional problems. Results: Children with NDDs, EBPs, and both NDDs and EBPs self-reported lower scores on general self-esteem. Children with NDDs and both NDDs and EBPs reported lower scores on peer relationships and prosocial behavior. Lastly, children with both NDDs and EBPs self-reported higher scores on anxiety-emotional behaviors. After considering family socio-demographic characteristics and parenting behaviors, these differences remained statistically significant only for children with both NDDs and EBPs. Child age and gender, household income and parenting behaviors were important in explaining these associations. Conclusions: Psychosocial functioning differs for children with NDDs and/or EBPs. Children with both NDDs and EBPs appear to report poorer psychosocial functioning compared to their peers with neither condition. However, it is important to consider the context of socio-demographic characteristics, parenting behaviors and their interactions to understand differences in children's psychosocial functioning. Implication for Rehabilitation: Practitioners may wish to consider complexity in child health by examining a comprehensive set of determinants of psychosocial outcomes as well as comorbid conditions, such as neurodevelopmental disorders (NDDs) and externalizing behavior problems (EBPs). Other health care professionals working with children with NDDs and/or EBPs may wish to consider several child characteristics together, not just the child's health conditions but also child sex and age. Developing specific intervention programs that improve the psychosocial functioning of children with complex health problems appears to be warranted.